DIGITALISASI PENDIDIKAN MELALUI PENERAPAN ICT BAGI SEKOLAH DI DESA SAENTIS KECAMATAN PERCUT SEI TUAN - Sudarma, Teguh Febri; Tanjung, Ratna; Junaidi, Agus (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
The SMK Center of Excellence (CoE) program targets 491 schools and 4,586 teachers and principals with a focus on developing improved learning in the world of work, teacher competence, and vocational school heads, as well as facilities and infrastructure. SMK Swasta PAB 12 Saentis is one of the 9 public and private vocational schools in North Sumatra developed by the Ministry of Education and Culture of the Republic of Indonesia through the Director General of Vocational Education to become a Center of Excellence in the Field of Hospitality in 2020. SMK Swasta PAB 12 Saentis which is located at Jl. Kali Serayau Desa/kelurahan Saentis Kecamatan Percut Sei Tua Kabupaten/Kota Deli Serdang Provinsi Prov. North Sumatra. SMK Private PAB 12 has an area of 41252 m2. However, SMK Swasta PAB 12 Saentis does not yet have a School Website that presents information related to school profiles, E-learning, and also graduate databases. the solution offered Create a school website that has e-learning, PPDB, and graduate tracing, as well as provide training on website utilization to administrative staff and provide training to teachers in managing learning using e-learning equipped with learning tools. After the Training Process is procured, the management of the school administration website can be independent in making an important article or information post. Teachers can already manage most of the e-learning of SMKS PAB 12 Scientists in filling learning content.